Maternal COVID-19 infection and risk of respiratory distress syndrome among newborns: a systematic review and meta-analysis - Muhammed Shabil; Shilpa Gaidhane; Suhas Ballal; Sanjay Kumar; Mahakshit Bhat; Shilpa Sharma; M Ravi Kumar; Sarvesh Rustagi; Mahalaqua Nazli Khatib; Nishant Rai; Mohammed Garout; Nabiha A. Bouafia; et al. (BMC Infectious Diseases)
Abstract Background The COVID-19 pandemic has significantly impacted public health, with emerging evidence suggesting substantial effects on maternal and neonatal health. This systematic review and meta-analysis aimed to quantify the prevalence and risk of respiratory distress syndrome (RDS) in newborns born to mothers infected with SARS-CoV-2, the virus responsible for COVID-19. Methods We conducted a literature search in Embase, PubMed, and Web of Science up to April 20, without language or date restrictions. Observational studies reporting on the prevalence or risk of RDS among newborns from mothers with confirmed SARS-CoV-2 infection were included. Quality assessment was performed using the JBI tool. Statistical analysis was performed by using R software version 4.3. Results Twenty-two studies met the inclusion criteria. The pooled prevalence of RDS among newborns born to COVID-19-infected mothers was 11.5% (95% CI: 7.4–17.3%), with significant heterogeneity (I² = 93%). Newborns from infected mothers had a significantly higher risk of developing RDS, with a pooled risk ratio (RR) of 2.69 (95% CI: 1.77 to 4.17). Conclusion Newborns born to mothers with COVID-19 have a substantially increased risk of developing RDS. These findings emphasize the need for vigilant monitoring and appropriate management of pregnant women with COVID-19 to mitigate adverse neonatal outcomes.